KAJIAN TINGKAT BAHAYA EROSI DI DAS SATUI, KABUPATEN TANAH BUMBU - Wahyuni Agustiningtiasih (Universitas Lambung Mangkurat, 2020)
The purpose of this study to analyze the magnitude of erosion, erosion4hazard class and erosion hazard level in some land cover located in the Satui watershed, Tanah Bumbu Regency. The4benefits of this research are expected to be able to provide information to relevant parties regarding the magnitude of the erosion hazard level (TBE), as a consideration in the framework of policy making in land management and utilization in the context of environmental preservation.The method used is descriptive analysis method that is taking existing data. Primary data includes data to determine soil erodibility obtained from the analysis of several physical properties of soil, namely soil structure, texture (content of sand, dust and clay), organic matter content, soil permeability. This data is obtained by taking predetermined soil samples taking into account the types of land cover, slope length and slope. Secondary data includes data about the general description of the location of the study, rainfall data and data on slope length and slope.The results of this study indicate that the amount of erosion that occurs in the Satui watershed has class I to IV and the value of the erosion hazard level starts from mild (I-R) to (III-B).Keywords: erosion; erosion hazard level; Satui watershed